Pengembangan Mantri Caino: Inovasi Media Pembelajaran Interaktif Berbasis Etnomatematika - Riska Nur Rohmah; Westi Ayu Maulida Permata Sari; Dimas Galih Dwi Pangasta; Agung Deddiliawan (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to produce Mantri Caino media, namely ethnomatematics-based interactive learning media, created by using Adobe Flash. Caino Mantri was intended for junior high school students (SMP) and equivalents. The method used in this study was research and development (R & D). In this method, several stages of Caino Mantri's quality measurements were carried out, including validity, practicality, and effectiveness. Based on the conducted research, it can be concluded that the product produced, namely interactive learning media Mantri Caino, has fulfilled the specified criteria, that was valid, practical, and effective to be used in learning. The conclusion found that Mantri Caino's interactive learning media were valid, practical, and effective. This was in accordance to the assessment of experts, student responses, and student test results, with 90% of students included in the complete category.